Syed Ahmad Khan’s twin objectives of educational reforms in British India: muslim advancement and Hindu-Muslim unity - Ali, Md. Yousuf; Bakar, Osman (IIUM Press, 2021)
The primary aim of this article is to discuss the twin objectives of Syed Ahmad Khan’s (1817-1898) religious and educational reforms during the British colonial rule, namely Muslim socio-cultural advancement and progress and the realisation of Hindu-Muslim unity. This study shows that Syed Ahmad’s approach to educational reforms was non-sectarian, but his special emphasis on Muslim education was dictated by the social fact that the Muslim community was backward compared to the Hindus and, moreover, they were suppressed by the British colonial rulers. Syed Ahmad is portrayed here as an advocate of Hindu-Muslim unity. His strategic approaches to the realisation of this unity were through education, both formal and informal. Formally, he built schools, colleges and universities that were meant to provide modern education and foster harmonious Hindu-Muslim relations. His informal education platform was civil society organisations in which he collaborated with Hindu leaders to promote intercultural understanding and communal solidarity. He also used his public office as a platform to serve the interests of all Indians. The article concludes with a suggestion on the need to revisit the issue of the significance of Syed Ahmad for both his and our times, particularly in the light of the inter-communal conflicts that ravaged present-day India.